Pengaruh Pemasaran TikTok pada Minat Beli Produk Optika Lunett dengan Mediasi Kesadaran dan Citra Merek - Nurhamidah, Isnaeni; Laksana, Dwi Hari (Forum Kerjasama Pendidikan Tinggi, 2025)
TikTok's social media marketing activities tend to increase and become a trend in the business world.This study analyzes the direct and indirect effects of TikTok's social media marketing activities onpurchase intention with brand awareness and brand image as mediating variables. The population inthis study were Indonesians aged more than 17 years. The number of samples taken was 100respondents. This study uses quantitative methods with purposive sampling techniques, and dataanalysis techniques using Structural Equation Modeling (SEM) then processed in SmartPLS 4.0 software. The results of the study indicate that social media marketing has a positive andsignificant effect on purchase intention, social media marketing has a positive and significant effecton brand awareness, social media marketing has a positive and significant effect on brand image,brand awareness has a positive and significant effect on purchase intention, brand image has noeffect on purchase intention, social media marketing affects purchase intention through brandawareness, and social media marketing has no effect on purchase intention through brand image.